Women, environmental changes and forestry-related development : gender-affected roles of rural people in land degradation and environmental rehabilitation in a dry region of Sudan - Eskonheimo, Anu, 1967- (Helsinki : University of Helsinki, 2006)
Suomenkielinen tiivistelmä.
Väitöskirja
Myös verkkoaineistona.
Keywords: maatalousmaa; metsätalousmaa; köyhyys; toimeentulo; maaseutuväestö; naiset; sukupuoli; metsänhoito; ympäristöohjelmat; kehitysohjelmat; ympäristönmuutokset; Afrikka; Sudan